Relative developmental and reproductive fitness associated with F1534C homozygous knockdown resistant gene in Aedes aegypti from Thailand - S. Plernsub (2018)
The effect of permethrin resistance, conferred by a homozygous mutation (F1534C) in the voltage-gated sodium channel protein, upon the reproductive fitness of Aedes aegypti (PMD-R strain) from Thailand was evaluated by comparing with a pyrethroid-susceptible subcolony (PMD strain). The parameters evaluated included larval development time, pupation success, adult emergence, egg production and hatchability, mating ability, female wing length and adult longevity. Larval development times were similar with very low mortality of larvae, pupae and emerging adults among either strain. However, PMD produced significantly fewer females than PMD-R. The mean numbers of eggs laid by PMD (54.2±15.9) and PMD-R (54.6±14.5) strains were not significantly different but the hatchability of PMD eggs (53.7%) was lower than PMD-R eggs (71.2%). The mean wing length of PMD females (2.85±0.15 mm) was longer than PMD-R females (2.74±0.09 mm). The insemination rates for both strains were 100%. The longevity of both strains was mostly not significantly different, over 90% of both sexes surviving at day 30. Our results suggest that the presence of the homozygous F1534C mutation does not lead to fitness reductions. This is in accordance with the high frequency of this allele found among wild populations of Ae. aegypti in many countries. These results also suggest that the removal of pyrethroid insecticide selection pressure may not lead to a regression of 1534C alleles in pyrethroid resistant Ae. aegypti.